THE INFLUENCE OF RECRUITMENT, SELECTION AND JOB PLACEMENT ON THE PERFORMANCE OF BANK BTN BRANCH OFFICES IN KARAWANG - Ayu Wulandari; Sari Marliani; July Yuliawati (Journal Of Resource Management, Economics And Business, 2024)
Purpose: To analyze the influence of recruitment, selection, and work placement on employee performance at PT. State Savings Bank (Persero) Tbk. Karawang Branch Office. Research Methodology: Quantitative verification method, population of 100 people with a sample of 80 employees, multiple linear regression analysis using SPSS version 25. Results: Recruitment, selection, and job placement have a partial and simultaneous influence on employee performance. Job placement has the most dominant influence on employee performance. Limitations: The study was conducted at a single branch office of the bank. Contribution: The findings can be useful for human resource management practices in the banking industry.